2016
DOI: 10.1039/c5ra20856d
|View full text |Cite
|
Sign up to set email alerts
|

Pyoverdin mediated sunlight induced green synthesis of silver nanoparticles

Abstract: The objective of this work was to check the ability of a siderophore, pyoverdin, a natural iron chelating compound of bacterial origin to produce silver nanoparticles (AgNps) under sunlight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The synthesized PVD-AgNPs have both spherical and non-spherical shapes. Previous studies reported that AgNPs generated via PVD from P. aeruginosa have a spherical [ 69 ] and face-centered cubic morphology [ 33 ]. The produced PVD-AgNPs were very stable, with a high zeta potential (−36.51 ± 0.69 mV), as shown by prior stability studies of AgNPs [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized PVD-AgNPs have both spherical and non-spherical shapes. Previous studies reported that AgNPs generated via PVD from P. aeruginosa have a spherical [ 69 ] and face-centered cubic morphology [ 33 ]. The produced PVD-AgNPs were very stable, with a high zeta potential (−36.51 ± 0.69 mV), as shown by prior stability studies of AgNPs [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…These biomolecules also act as a corona that surrounds the NPs, supporting their endurance and bio-compatibility [ 31 , 32 ]. In addition, the corona layer over the NPs enhances its biological effectiveness by interacting with the cell membrane, followed by internalization [ 33 ]. Hence, to control biofilm-forming microbial pathogens, if the corona is derived from the microbial species, that can help in the interaction with the cell surface of the microbial pathogen that might have similar components matching with the corona [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the Arnow’s test gives ambiguous results with these molecules, despite bearing a catechol function. While most authors report that PVDs do not react positively to this test [ 37 , 73 ], there is no shortage of evidence that PVDs give positive results with both Csaky’s and Arnow’s assays, indicative of mixed-type siderophores [ 158 ].…”
Section: Analytical Methods For the Identification Of Pvdsmentioning
confidence: 99%